Identifying Support for Knowledge-Intensive Processes in BPMN and its Extensions - Nunes, Mariano de Oliveira; Pillat, Raquel Mainardi; Oliveira, Toacy Cavalcante de (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: Business process modeling is widely used to increase the competitive advantage of organizations and Business Process Model and Notation (BPMN) is the standard language for modeling such processes. However, it is often extended to handle domain-specific processes or enhance the language itself. Problem: Applications of process-oriented approaches have reached new challenging, knowledge-intensive scenarios, such as healthcare, case management, and others. For these scenarios, it is common to observe functions involving collaborative resources and processes that are little structured, which do not have the same level of predictability as a structured work routine. This fact led to the definition of a new class of business processes, Knowledge-Intensive Processes (KIP). Solution: This paper investigates which requirements related to the modeling of KIP are met by the standard BPMN language and its extensions proposed in the literature. IS Theory: The paper explores the interaction between Structured Process Modeling Theory and Organizational Information Processing Theory applied to the context of business process management, especially related to knowledge-intensive processes in organizations. Method: We performed an analysis of the adherence of standard BPMN to the KIP modeling requirements and a systematic literature review identifying BPMN extensions, analyzing these proposals regarding their adherence to the same requirements. Summarization of Results: Twelve BPMN extensions were analyzed and compared according to a set of criteria. These extensions were obtained from the SCOPUS digital library and guided the conduct of the research. Contributions and Impact in the IS area: This paper is the first evaluation of BPMN and its extensions regarding KIP requirements. Moreover, we identified the main trends in the development of BPMN extensions related to KIP and some opportunities for future researches.